The Qur'anic Perspective On The Science Of Water Transportation - Yusuf Abdul Azeez; Mansoureh Ebrahimi; Abdullahi Saliu Ishola; Ahmad Tijani Surajudeen (Nova Explore Publications, 2024)
From Islam’s inception Muslims have believed that The Glorious Qur’an is not only a final revelation sent by Almighty Allah to cater for all aspects of human life but also a canonical book of law containing a series of Scientific discoveries that guide the advancement of human enterprise and business endeavours. This study examines diverse elements on the science of water transportation from the Qur’anic perspective that encompasses processes of the planet’s water cycle as to how water is formed and maintained after loss through evaporation. An attempt is made to discuss the importance of the science of water transportation in the light of verses taken from The Glorious Qur’an, including its description of the cycle, basic physical components, as well as hazards and threats likely to occur during the course of transport.